Food Allergy and Physiology: A Review Article: Alergi Makanan dan Fisiologi: Sebuah Artikel Ulasan - Hamid, Samahir Sabri (Universitas Muhammadiyah Sidoarjo, 2025)
Given the rising incidence of allergies, Proteins, either in their natural state or in forms arising from food preparation, are the source of food allergies. The field of proteomics has substantially benefited from advancements in mass spectrometry. These developments round out the range of biological assays that have been employed up to this point, including PCR and ELISA, and enable the identification and measurement of allergenic protein traces in complicated mixtures. We highlight significant advancements in mass-spectrometric techniques and examine approaches categorized based on their capacity to simultaneously quantify and detect allergenic proteins Highlights: Proteomics Advancements – Mass spectrometry improves allergen detection in food. Diagnostic Methods – ELISA, PCR, and immunoassays enhance allergen identification. Regulations – European laws mandate allergen labeling on food products. Keywords: Food allergies, proteomics, mass spectrometry, ELISA, PCR